A life cycle assessment model for quantification of environmental footprints of a 3.6 kWp photovoltaic system in Bangladesh - Md. Mustafizur Rahman; Chowdhury Sadid Alam; TM Abir Ahsan (Center of Biomass & Renewable Energy, Diponegoro University, 2019)
Life cycle assessment (LCA) is an extremely useful tool to assess the environmental impacts of a solar photovoltaic system throughout its entire life. This tool can help in making sustainable decisions. A solar PV system does not have any operational emissions as it is free from fossil fuel use during its operation. However, considerable amount of energy is used to manufacture and transport the components (e.g. PV panels, batteries, charge regulator, inverter, supporting structure, etc.) of the PV system. This study aims to perform a comprehensive and independent life cycle assessment of a 3.6 kWp solar photovoltaic system in Bangladesh. The primary energy consumption, resulting greenhouse gas (GHG) emissions (CH4, N2O, and CO2), and energy payback time (EPBT) were evaluated over the entire life cycle of the photovoltaic system. The batteries and the PV modules are the most GHG intensive components of the system. About 31.90% of the total energy is consumed to manufacture the poly-crystalline PV modules. The total life cycle energy use and resulting GHG emissions were found to be 76.27 MWhth and 0.17 kg-CO2eq/kWh, respectively. This study suggests that 5.34 years will be required to generate the equivalent amount of energy which is consumed over the entire life of the PV system considered. A sensitivity analysis was also carried out to see the impact of various input parameters on the life cycle result. The other popular electricity generation systems such as gas generator, diesel generator, wind, and Bangladeshi grid were compared with the PV system. The result shows that electricity generation by solar PV system is much more environmentally friendly than the fossil fuel-based electricity generation. ©2019. CBIORE-IJRED. All rights reserved